Development of the Tools for the Assessment of the Influence of Administrative Regulation on the Business Efficiency in the Region - Natalia Zinovyevna Solodilova; Rustam Ilkamovich Malikov; Konstantin Evgenyevich Grishin (Экономика региона, 2016)
The article discusses the theoretical issues of the formation of the administrative regulation mechanisms for business entities. The necessity of the further development of theoretical and methodological base and the application toolkit for the design of business environment is proved. This can stimulate the growth of business and investment activity in the Russian regions and municipalities. The authors identify two types of government structures influence on the business entities, differentiated by the nature of the targeting impact on the economic activity of business structures — the administrative pressure and administrative assistance. It is suggested that in practice, high cost implications for compliance with all regulation requirements as well as sanctions for the violation of these requirements create preconditions for the development of informal interaction between entrepreneurs and the representatives of regulatory bodies. Therefore, businessmen try to minimize the costs associated with the implementation of formal administrative requirements, rules and regulations by personal arrangements. A mathematical model for the assessment of the informal interaction between business entities and certain officials of control supervisory authorities is proposed. It allows to determine the range of benefits for economic entities from avoiding the implementation of administrative norms, requirements and rules. It is concluded that unreasonably high level of costs for the implementation of formal administrative requirements rules and regulations by business entities composes the economic basis for the reproduction of informal relations. This determines mutual benefits for a number of entrepreneurs and a part of bureaucracy from various schemes of informal interaction.